ANALISIS SWOT KERAGAMAN BUDAYA INDONESIA - Widiastuti, - (Lembaga Layanan Pendidikan Tinggi Wilayah III Jakarta, 2013)
Indonesia as an archipelagic country with various ethnic groups which has the diversity of thinking, art, religion, science, languages and traditions of the local cultures with unique n different characteristics. The objective of this study is to analyze the Indonesian cultural diversity by using SWOT analysis. The methods used library research with descriptive explorative approaches. it is concluded that: (1) The differences arising from cultural diversity has the potential as a nation to build strength, (2) The weaknesses arising from the lack of understanding of the cultural values to trigger conflict, (3) The opportunities arise when working together despite the different cultures in order to face the globalization, (4) As the challenges to respond and to manage the value of local and global competition so as to maintain the existing culture.